Survey of Microbial Diversity in Flood Areas during Thailand 2011 Flood Crisis Using High-Throughput Tagged Amplicon Pyrosequencing. - Wuttichai Mhuantong; Sarunyou Wongwilaiwalin; Thanaporn Laothanachareon; Lily Eurwilaichitr; Sithichoke Tangphatsornruang; Benjaporn Boonchayaanant; Tawan Limpiyakorn; Kobchai Pattaragulwanit; Thantip Punmatharith; John McEvoy; Eakalak Khan; Manaskorn Rachakornkij; et al. (PLoS ONE, 2015)
The Thailand flood crisis in 2011 was one of the largest recorded floods in modern history, causing enormous damage to the economy and ecological habitats of the country. In this study, bacterial and fungal diversity in sediments and waters collected from ten flood areas in Bangkok and its suburbs, covering residential and agricultural areas, were analyzed using high-throughput 454 pyrosequencing of 16S rRNA gene and internal transcribed spacer sequences. Analysis of microbial community showed differences in taxa distribution in water and sediment with variations in the diversity of saprophytic microbes and sulfate/nitrate reducers among sampling locations, suggesting differences in microbial activity in the habitats. Overall, Proteobacteria represented a major bacterial group in waters, while this group co-existed with Firmicutes, Bacteroidetes, and Actinobacteria in sediments. Anaeromyxobacter, Steroidobacter, and Geobacter were the dominant bacterial genera in sediments, while Sulfuricurvum, Thiovirga, and Hydrogenophaga predominated in waters. For fungi in sediments, Ascomycota, Glomeromycota, and Basidiomycota, particularly in genera Philipsia, Rozella, and Acaulospora, were most frequently detected. Chytridiomycota and Ascomycota were the major fungal phyla, and Rhizophlyctis and Mortierella were the most frequently detected fungal genera in water. Diversity of sulfate-reducing bacteria, related to odor problems, was further investigated using analysis of the dsrB gene which indicated the presence of sulfate-reducing bacteria of families Desulfobacteraceae, Desulfobulbaceae, Syntrobacteraceae, and Desulfoarculaceae in the flood sediments. The work provides an insight into the diversity and function of microbes related to biological processes in flood areas.